'Drinking the Kool-Aid' of cult TV: Fans, followers, and fringe religions in Strangers with Candy and Veronica Mars. (1st October 2013) - Diffrient, David Scott
This article explores episodes of the contemporary American television programmes Strangers with Candy (Comedy Central, 1999–2000) and Veronica Mars (UPN/CW, 2004–07) so as to ascertain and discursively frame the complex relationship between cults (or neo-religious organizations) and cult TV. Although different from one another in many respects, these two TV series share an interest in the cliquish formations of high-school life that divide students into warring camps of insiders and outsiders. Moreover, both programmes contain pivotal episodes in which the ritualistic practices of fictional cults are presented ambivalently – as a source of humour yet also as a gateway through which the unconventional female protagonists pass on their way to self-discovery. That journey has extraordinary resonance for fans or 'followers' of these programmes. As argued by Jonathan Gray in his recently published work on 'affect, fantasy, and meaning', fans and followers are viewers who are 'most involved in their consumption'. As such, Strangers with Candy and Veronica Mars deserve scrutiny as steadfastly worshipped texts conducive to the kinds of meta-consumptive discourses and practices that might shed light on culturally entrenched attitudes related to neo-religious activities.